Interval cancers in a FOBT-based colorectal cancer population screening programme: implications for stage, gender and tumour site. Issue 4 (19th September 2011) - Steele, R J C; McClements, P; Watling, C; Libby, G; Weller, D; Brewster, D H; Black, R; Carey, F A; Fraser, C G
Abstract : Background: Between 2000 and 2007, a demonstration pilot of biennial guaiac faecal occult blood test (GFOBT) screening was carried out in Scotland. Methods: Interval cancers were defined as cancers diagnosed within 2 years (ie, a complete screening round) of a negative GFOBT. The stage and outcome of the interval cancers were compared with those arising contemporaneously in the non-screened Scottish population. In addition, the gender and site distributions of the interval cancers were compared with those in the screen-detected group and the non-screened population. Results: Of the cancers diagnosed in the screened population, interval cancers comprised 31.2% in the first round, 47.7% in the second, and 58.9% in the third, although this was due to a decline in the numbers of screen-detected cancers rather than an increase in interval cancers. There were no consistent differences in the stage distribution of interval cancers and cancers from the non-screened population, and, in all three rounds, both overall and cancer-specific survival were significantly better for patients diagnosed with interval cancers (p<0.01). The percentage of cancers arising in women was significantly higher in the interval cancer group (50.2%) than in either the screen-detected group (35.3%, p<0.001) or the non-screened group (40.6%, p<0.001). In addition, the proportion of both right-sided and rectal cancers was significantly higher in the interval cancer group than in either the screen-detected (p<0.001) or non-screened (p<0.004) groups. Conclusions: Although GFOBT screening is associated with substantial interval cancer rates that increase with screening round, the absolute numbers do not. Interval cancers are associated with a better prognosis than cancers arising in a non-screened population, and GFOBT appears to preferentially detect cancers in men and the left side of the colon at the expense of cancers in women and in the right colon and rectum.